Speech Disorder in an 11 Years Old Child with Intellectual Disability in Rumah Tiga Village - Sekewael, Pricilia; Rumalean, Iwan; Tabelessy, Novita (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the speech disorder of an 11-year-old intellectually disabled child in Rumah Tiga Village, Teluk Ambon District, Ambon City. The type of research used is descriptive qualitative research. This is a qualitative approach that uses humans as the research instrument. The research findings are that speech disorders in an 11-year-old mentally disabled child in Rumah Tiga village, Teluk Ambon sub-district, Ambon city, are classified based on: (a) Substitution, (b) Omission, and (c) Addition